2022
DOI: 10.1002/hec.4484
|View full text |Cite
|
Sign up to set email alerts
|

The health returns of attending university for the marginally eligible student

Abstract: A key policy question is whether continued expansion of university education is beneficial for the marginally eligible student. In this paper we exploit an arbitrary university eligibility rule combined with regression discontinuity design to estimate the causal effect of university attendance on healthcare utilization amongst young adults in Sweden. We find that the eligibility rule leads to a clear jump in university attendance of between 10% and 14% points for both males and females. 2SLS estimates find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The study found that a 10% increase in university admission rates might lead to a 1% increase in hospital admissions for male students on the edge of admission eligibility, with the underlying reason being mental illnesses related to alcohol and narcotics. However, an opposite phenomenon was observed among female students, where university education reduced the probability of hospitalization due to mental health issues for female students (Heckley et al, 2022).…”
Section: Health Behaviormentioning
confidence: 94%
“…The study found that a 10% increase in university admission rates might lead to a 1% increase in hospital admissions for male students on the edge of admission eligibility, with the underlying reason being mental illnesses related to alcohol and narcotics. However, an opposite phenomenon was observed among female students, where university education reduced the probability of hospitalization due to mental health issues for female students (Heckley et al, 2022).…”
Section: Health Behaviormentioning
confidence: 94%
“…Specifically, we investigate the impact on mental ill‐health among young adults which is, around the world, seen as one of the largest public health challenges in modern times (United Nations Children's Fund, 2021 ). We hypothesize that over‐grading impacts the production of mental health through (1) a direct effect of performance feedback, (2) an impact on self‐efficacy beliefs by which positive feedback/re‐ranking increases self‐confidence, motivation and performance thereby positively affecting mental health, or (3) through the admission distortion which increases opportunities for higher education investments, of which both attendance and years completed have been found to causally affect health (Buckles et al., 2016 ; Heckley et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%